PENGARUH KECEMASAN SAAT PANDEMI COVID 19 TERHADAP KETERATURAN PEMERIKSAAN MASA NIFAS - Windarti, Yunik; Rizki, Lailatul Khusnul (Care : Jurnal Ilmiah Ilmu Kesehatan, 2021)
The covid-19 pandemic is still not over despite various efforts that have been made. Fear of contracting this virus caused some people to experience anxiety. These restrictions on movement space and health protocols narrow the space for postpartum mothers to check themselves in health services. The purpose of the study was to analyze the effect of anxiety during the covid 19 pandemic on the regularity of the postpartum examination. Non-experimental research design: cross sectional analytic, the independent variable is anxiety, the dependent variable is the regularity of the postpartum examination. The population and sample of postpartum mothers were 45 respondents, the sampling technique was incidental sampling in Wonokromo Village. The data were analyzed using Spearman's test. The results showed that of the 22 respondents with mild anxiety levels, almost all (90.9%) had regular postnatal check-ups. The value of p = 0.021 0.05 means that there is a significant effect. It can be concluded that the less anxious mothers are during the covid-19 pandemic, the more it will affect the regularity of postpartum mothers in checking themselves in health services. Postpartum mothers are expected to be able to control anxiety and continue to check themselves by complying with health protocols.